The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.socscimed.2016.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Common or multiple futures for end of life care around the world? Ideas from the ‘waiting room of history’

Abstract: Around the world there is growing interest in the manner in which care is delivered to people at the end of life. However, there is little unanimity on what constitutes a ‘good death’ and the appropriate societal responses to the issue of delivering culturally relevant and sustainable forms of end of life care in different settings are not subjects of broad agreement. In this critical conceptual paper we focus on the emerging narratives of global palliative care and offer an assessment of their implications. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
69
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 46 publications
(46 reference statements)
0
69
0
2
Order By: Relevance
“…Differences in social and cultural values can be brought to the forefront when confronting medical decision‐making, especially related to end‐of‐life care (Zaman et al, ). In a systematic review of 102 studies, Frost and colleagues concluded that patient and clinician race, ethnicity and nationality are associated with the level of intensity of end‐of‐life ICU treatment.…”
Section: Introductionmentioning
confidence: 52%
“…Differences in social and cultural values can be brought to the forefront when confronting medical decision‐making, especially related to end‐of‐life care (Zaman et al, ). In a systematic review of 102 studies, Frost and colleagues concluded that patient and clinician race, ethnicity and nationality are associated with the level of intensity of end‐of‐life ICU treatment.…”
Section: Introductionmentioning
confidence: 52%
“…A gap in the knowledge of priorities representing those in lower and middleincome countries (LMIC) exists, echoing previous reviews of international palliative care research [66,67]. Whilst there is evidence in this review of engagement, with researchers from high-income regions collaborating and undertaking research in Africa (Powell et al, 2014), a number of researchers [31,67] suggest this raises multi-faceted challenges including the risk of imposing western norms in differing cultural contexts [68]. Therefore, the application of western research priority findings is limited, if not adapted to the specific economic, cultural and specific health care context and constraints of lower-and middle-income countries.…”
Section: What Is Already Known and What Does This Review Addmentioning
confidence: 73%
“…Therefore, the application of western research priority findings is limited, if not adapted to the specific economic, cultural and specific health care context and constraints of lower-and middle-income countries. Zaman et al [31] suggests the need for LMIC to initially develop culturally and locally appropriate research, and then move towards international comparative research.…”
Section: What Is Already Known and What Does This Review Addmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of palliative care interventions to relieve suffering in the context of advanced disease and in the face of death, has gained policy, clinical and academic endorsement worldwide 1, 2 . Beginning in the 1960s with the emergence of new hospice programmes, the modern field of palliative and end of life care grew rapidly in the later decades of the twentieth century and has continued to make progress, attracting wide interest and support, and extending its reach 3 .…”
Section: Introductionmentioning
confidence: 99%